(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The aim of this experiment was to create an innovative and simple HHO gas production system to investigate its effect on engine performance and exhaust emissions and to determine whether hydroxyl gas could be a viable and sustainable solution for reducing fuel consumption and pollutant emissions. Compared to various hydrogen production processes, electrolytic hydrogen is cheaper and has a lower environmental impact when it is produced by the electrolysis of water. A hydrogen generator was designed and built to produce gas HHO by electrolysis of distilled water in the presence of a catalyst (NaOH) as an electrolyte, using a pulse-width modulation (PWM) production system to control the amount of gas. Tests were carried out on a single-cylinder, four-stroke petrol engine (PRODIT GR306/0001). Gas was added to the engine’s air intake manifold at different flow rates. Tests are conducted at 2000 rpm and compression ratios(11:1)under various loads. Test results show an improvement in engine performance through an increase in thermal efficiency at best case (12%), a reduction in fuel consumption by (15.3%), and a reduction in all exhaust emissions (CO2, CO, HC, and O2). It was also noted that the exhaust gas temperature is lower when operating on dual fuel compared to pure gasoline.